Description of the novel KIR2DL4*035 allele identified using high‐throughput sequencing. (24th February 2016) - Alicata, C.; Bottino, C.; Guethlein, L. A.; Parham, P.; Norman, P. J.
Abstract : A newly identified allele of the KIR2DL4 natural killer cell receptor for human leukocyte antigen (HLA) class I.